Math, asked by yashwnthbhai14, 4 months ago

Solve the following equation : 15(x-1)+4(x+3)=2(7+x)


Answers

Answered by straightforward
0

Step-by-step explanation:

15(x - 1) + 4(x  + 3) = 2(7 + x) \\ 15x - 15 + 4x + 12 = 14 + 2x \\ 15x + 4x - 15 + 12 = 14 + 2x \\ 19x - 3 = 14 + 2x \\ 19x - 2x = 14 + 3 \\ 17x = 17 \\ x =  \frac{17}{17}  \\ x = 1

hope it helps you

pls Mark this answer as the brainliest

Answered by PurvaAnantwar
0

Step-by-step explanation:

you can solve it like this as shown above by me !

hope this helps you!

Attachments:
Similar questions